Understanding and overcoming the barriers to structural steel reuse, a UK perspective. (1st April 2017) - Densley Tingley, Danielle; Cooper, Simone; Cullen, Jonathan
Abstract: To meet greenhouse gas emission targets, at global, national and sector level, reduction opportunities should be explored in both the embodied and operational carbon of the built environment. One underexploited option to reduce embodied carbon is the reuse of structural steel. However, in the UK, work by Sansom and Avery (2014) suggests a picture of declining levels of reuse. This paper explores why this is the case by identifying the practical barriers to structural steel reuse through a series of semi-structured interviews with UK construction industry members. Whilst there were many identified barriers, five practical barriers were prioritised as being most significant: cost, availability/storage, no client demand, traceability and supply chain gaps/lack of integration. These contrast with those most commonly identified in global literature: cost, supply chain gaps/integration, risk, jointing technique, composite construction and time for deconstruction; with only two overlaps: cost and supply chain gaps/integration. Many of the barriers from literature have a technical focus (reducing salvage yield rather than completely preventing reuse) differing from the largely systemic barriers that the interviews prioritised. These systemic barriers will need to be dealt with first to increase reuse rates. This will require a coordinated approach across the UK construction supply chain. Building on interview insights, this paper proposes four mechanisms to overcome these systemic barriers: (1) the creation of a database of suppliers/reused section availability, (2) a demonstration of client demand (3) technical guidance and education for the construction industry and (4) government leadership. Together these mechanisms would improve reuse rates in the UK, reduce the embodied emissions of the built environment and play a crucial role in meeting greenhouse gas emissions reduction targets. Highlights: 5 significant barriers to structural steel reuse identified in interviews. Barriers are systemic requiring a coordinated, whole supply chain approach. They differ from commonly identified technical barriers in existing literature. 4 mechanisms to overcome the systemic barriers are presented and discussed.